Microplásticos em praias flúvio-estuarinas amazônicas - NOVAES, Gabriela de Oliveira (2019)
The types of microplastics (particles smaller than 5 mm) most common in coastal environments, such as estuarine beaches, are the fibers. These particles mainly occur due to fishing activity, local users and human occupation. In the last years, several studies have been carried out to provide initial information on microplastic characteristics and their distribution in different environments. However, those studies are related to oceanic beaches, without records of studies on Amazonian estuarine-fluvial beaches. The objective of this work is to evaluate the distribution of microplastics in estuarine Amazonian beaches. Sediments were collected on five beaches of the Cotijuba island. Sampling was performed using the trench method, which measured 50 x 50 cm, with a maximum depth of 80 cm. Each trench was divided into four layers of 20 cm. Also, superficial sediments were sampled in the high tide line, over an area of 40 x 40 cm. The microplastics were classified according to type, color, and shape. A total of 13,007 microplastics were found in the trenches, in which 99.6% were fibers. In the superficial samples, 883 particles were verified. Also, most of them were fibers. The fiber densities are significantly different between the beaches, between the layers and reflect the type of use of the beaches. The dominant source of pollution on Cotijuba island beaches is the fishing activities, common in the region. However, the use of beaches by tourists, as well as the intense local hydrodynamics can interfere in the deposition of microplastics in the beach sediment.